Era Digitalisasi Media Pemasaran Online dalam Gugurnya Pasar Ritel Konvensional - Afifatur Rohimah (Universitas Muhammadiyah Sidoarjo, 2018)
Digital communication era has impacts on the life, one of them is in the world of marketing communications. Based on data obtained, it was started in the end of 2016 to early 2017 that became the beginning of the turmoil of the modern retail market. One by one the modern retail market fell because modern society was not only to want comfortable shopping activities and places, but also practical and efficient. This was offered by online shopping, a lot of benefits coulbe be gains, such as making people prefer to online shopping activities rather than shopping conventionally. There were many benefits that offered by online shopping, the modern retail market should anticipate and implement several programs to maintain its existence in the market. It aims to make the life of the modern retail market more exist. In the era of the development of digitalization of communication needs alternative way to anticipate unexsistansion in society. So, that was no longer the process of fall of the conventional market in the digital era.